ANALISA PERBANDINGAN PENGUKURAN ENERGI PADA kWh METER PASCABAYAR DAN kWh METER PRABAYAR - Andre, Gusrulli; Yulisman, Yulisman; Kamil, Mahyessie (Ensiklopedia Research and Community Service Review, 2024)
In this day and age, electricity plays a very important role in life. It can be said that electricity has become the main energy source for every activity in households and industry. The author will conduct comparative analysis research on power usage in postpaid kWh and prepaid kWh. This research aims to determine the cost of the two kWh meters and which of the two kWh meters is more effective. This research was conducted from 20 December 2023 to 25 January 2024. This research was conducted in Jalan Bantiang Village, Malalak District, Agam Regency, West Sumatra, Indonesia. Data collection was carried out by carrying out measurement experiments with the same load and interviewing customers using that type of kWh. After research was carried out, the results obtained were relatively the same when viewed from the cost of using electricity using the same load. Meanwhile, in terms of effectiveness in terms of the level of security, prepaid kWh is safer than postpaid kWh.Keywords: comparison of postpaid and prepaid kWh, effectiveness.